Menggunakan Strategi Outline pada Penulisan Esai Bagi Siswa ELT - Siti Fatimah Al Islamiah; Dina Merris Maya Sari (Universitas Putera Batam, 2021)
This research discusses the outlining strategy that applied in the ELT students’ essay writing class 2019 A English Education Program STKIP PGRI Sidoarjo which amounted to 10 students. The instruments used in this study were checklist observation and questionnaires. The data technique used is qualitative data, where the data will be described. The first research instrument, the researcher used a checklist observation form for implementation assessment by observing the class writing essays and participating in learning activities from beginning to end whose data was described in a table with a tick, the results showed that many activities were carried out by students in the classroom to improve their abilities in writing essays through an outlining strategy. The next instrument is a questionnaire for response assessment, the researcher asks for data from ELT students via a google form containing 15 yes or no questions. The results of the questionnaire showed that 90% of students answered yes, and 10% of students answered no. The results showed that the implementation and response of students were very positive and good during the learning activities to write essays using the outlining strategies of ELT students.